Evaluation of root zone cooling system for strawberry (Fragaria x ananassa duchesne) cultivation in tropical lowlands - Zainol Abidin, Mohd Ashraf (2015)
Strawberry prices have increased significantly due to high demand. In Malaysia's tropical climate, strawberries are only able to grow in highland areas which have low environmental temperatures. However, the areas are limited and strawberries are now can be grown inside greenhouses under a controlled environment in lowland areas. This has a high cost of production, thus reducing profits. Since root zone temperature (RZT) manipulation provides more benefits than environment temperature manipulation, a root zone cooling (RZC) system integrated with multi-tier cultivation technique (MCT) under fluctuating environment temperature located in lowland areas was proposed as an alternative method to cultivate strawberries. To evaluate the efficiency of the system proposed, three different treatments were set up. Treatment 1 and Treatment 2 were set up in lowland areas with and without the integration of RZC system. Treatment 3 was located in highland area without RZC system. All treatments were left to undergo fluctuating environmental conditions. On average, the environment temperature in lowland and highland areas were 28.91 °C and 20.71 °C respectively. For relative humidity, those values were 75.01% and 75.79%. Both areas experience around twelve hours of day light. However, lowland areas receive lower ventilation rates than highland areas. The use of RZC system reduced RZT down to 9.48% and increased the root zone moisture content (RZMC) up to 30.36%. The cooling system also was able to highly standardize the RZT at various points of the cultivation structure. Aside from potentialuation, a mathematical model for predicting RZT using minimum input data (environment temperature and chilled pipe temperature) was proposed and validated. The constants a and b were 2.83 x 10-8 W/K4 and 1.52785 W/K respectively. Though the treatment in the highland areas obtained better results in terms of fruit size, RZC system significantly increased the fruit’s diameter and weight up to 8.85% and 21.60% respectively for lowland productions. Moreover, 70.00% of the strawberries produced were of marketable size (> 5 g) compared to 46.67% of the strawberries produced by the treatment without RZC system. The lowland areas also produced more than 70.00% of the strawberries that above the average sweetness of the Festival variety (brix index: > 8 °Bx), compared to approximately 50.00% of the strawberries produced in the highland areas. In conclusion, the RZC system was found to significantly reduce RZT, and increase the RZMC. It also produces better fruit yield in strawberry cultivation in lowland areas, thus providing an alternative solution that can comply with the growing strawberry demand.